Kryzysy finansowe a bezpieczeństwo działalności banków komercyjnych - Stola, Emilia (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2015)
Financial crises which cause stagnation and economic recession are an inevitable part of economic reality of the world. Along with the globalization of financial markets both the number of crises and their reach increased. The last of the greatest economic breakdowns was “Crisis of the Euro” and “Global Financial Crisis 2008” which started the United States of America. They were caused by too gentle monetary and fiscal policy, which resulted in low interest rates and a lack of the budget and fiscal discipline. The aim of this study was to estimate and the evaluate interdependencies between the negative influence of economic-financial crises and the safety of commercial banks functioning in the Polish banking sector. Undertaken examinations allowed to check whether there are any statistical relations between the solvency ratio (reflecting the level of the bank safety) and the participation of irregular amounts due in the volume of credit on one hand and the changes of GDP and changes of stock exchange indices on the other. The analysis was carried out on data concerning commercial banks functioning in Poland and quoted on the Warsaw Stock Exchange.